Interassociation consensus statement on cardiovascular care of college student-athletes. Issue 2 (31st May 2016) - Hainline, Brian; Drezner, Jonathan; Baggish, Aaron; Harmon, Kimberly G; Emery, Michael S; Myerburg, Robert J; Sanchez, Eduardo; Molossi, Silvana; Parsons, John T; Thompson, Paul D
Abstract : Cardiovascular evaluation and care of college student-athletes is gaining increasing attention from both the public and medical communities. Emerging strategies include screening of the general athlete population, recommendations of permissible levels of participation by athletes with identified cardiovascular conditions and preparation for responding to unanticipated cardiac events in athletic venues. The primary focus has been sudden cardiac death and the usefulness of screening with or without advanced cardiac screening. The National Collegiate Athletic Association convened a multidisciplinary task force to address cardiovascular concerns in collegiate student-athletes, and to develop consensus for an interassociation statement. This document summarises the task force deliberations and follow-up discussions, and includes available evidence on cardiovascular risk, preparticipation evaluation and the recognition of and response to cardiac arrest. Future recommendations for cardiac research initiatives, education and collaboration are also provided.